The Impact of the Use of Pivotal Training in Some Physical Abilities and Skill of Handball for Students of the Department of Physical Education and Sports Sciences - Joudah, Younus Kadham (Pubmedia Jurnal Pendidikan Olahraga, 2026)
Handball is one of the sports that receive wide attention in all countries of the world for its enthusiastic nature and skills,Therefore, the organizers strive to exert their thought and effort to try to develop and raise its level using all modern training methods and scientific methods, including the core Training method, which is one of the basic pillars in modern sports training, especially in handball sports that require balance and exceptional axial strength, and handball requires fast and explosive movements and sudden changes in direction, jumping, throwing, and physical collision, and the axial muscles (the core muscles in the trunk) a force carrier extremities, making them necessary to perform most sports skills in handball, has emerged As an attempt to develop performance and develop physical abilities and skills for students, a set of exercises using the axial training method has been developed as a comprehensive, intensive and scientifically studied training program that contributes significantly to increasing and developing physical abilities and improving their performance of skills in competitions, and the research problem crystallized around weakness in the body structure and the axial muscles of the players, and the researcher considered seeking to use a training method to increase the strength of the axial muscles of the trunk and limbs, which is a method aimed at developing muscle strength in the axial muscles of the trunk, abdomen, upper and lower limbs, as well as for working muscles, noting its reflections in the results of the research variables, the goal of the research is to identify The researcher adopted the experimental method as the most suitable for the nature of the research, with an experimental design, one group and a research community of students of the Faculty of basic education / Mustansiriya University, the sample number was (15) players and (3) players were excluded for not continuing training, so the sample became (12 players) continued training during the duration of the experiment, as they were chosen by the sample Method intentionally because of its suitability to the research conditions and goals, and the researcher concluded the gastric axial exercises.